The effect of streptomycin, oxytetracycline, tilmicosin and phenylbutazone on spermatogenesis in bulls. - Barth, A D (1998)
To determine whether declining semen quality associated with health problems may be due to certain antibiotic or anti-inflammatory treatments, semen was collected 3 times per week for up to 42 d from 6 normal bulls after treatment with oxytetracycline, tilmicosin, dihydrostreptomycin, or phenylbutazone. No adverse effects on semen quality were observed.